2019
DOI: 10.1097/mrr.0000000000000324
|View full text |Cite
|
Sign up to set email alerts
|

Effects of capacitive and resistive electric transfer therapy in patients with knee osteoarthritis: a randomized controlled trial

Abstract: Capacitive and resistive electric transfer (CRET), an endogenous diathermy treatment, has been demonstrated to reduce pain and improve quality of life in numerous orthopedic degenerative and inflammatory problems but not in knee osteoarthritis (KOA). The aim of this prospective randomized controlled trial was to evaluate whether a 2-week program of CRET can reduce pain, stiffness and functional limitations in KOA compared with a sham treatment. Patients with KOA were randomly assigned to a study group (n = 31)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 19 publications
1
34
0
1
Order By: Relevance
“…Capacitive and resistive electric transfer therapy (CARE), an endogenous diathermic treatment, reduces pain and improves quality of life for several orthopaedic degenerative and inflammatory problems. 1 Its positive effects include greater blood circulation, which allows the removal of inflammatory catabolites. 2,3 Bito et al 4 reported that CARE substantially improves blood circulation in the peritendinous region and increases haemoglobin saturation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Capacitive and resistive electric transfer therapy (CARE), an endogenous diathermic treatment, reduces pain and improves quality of life for several orthopaedic degenerative and inflammatory problems. 1 Its positive effects include greater blood circulation, which allows the removal of inflammatory catabolites. 2,3 Bito et al 4 reported that CARE substantially improves blood circulation in the peritendinous region and increases haemoglobin saturation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, microwave diathermy works only at high temperatures and is thus indicated preferentially for post-acute and chronic phases. 1,9 Rotator cuff tendinopathy is the most common painful non-traumatic shoulder condition, affecting approximately 20% of the population and increasing in prevalence with age. 10,11 As the pain assumes the characteristics of an acute condition, CARE therapy could be a useful tool in the rehabilitation of this condition.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the horses were subjected to only four sessions and probably a higher number of sessions would have resulted in more evident accelerometric changes. In fact, between 6 and 10 sessions have been reported to result in improved function and disability and reduced pain in human beings with low back pain [21], myofascial chronic pain [22], knee osteoarthritis [23,38] and shoulder impingement syndrome [39].…”
Section: Discussionmentioning
confidence: 99%
“…The CRET group was subjected to a total of four CRET sessions, applied 2 days/week, during 2 consecutive weeks. The number of sessions per week was chosen on the basis of previous clinical reports in human patients with different musculoskeletal disorders, which described improved function and reduced pain when this therapy was applied 2-3 days/week [21][22][23]. Sedation was not needed for the treatment.…”
Section: Procedures Therapiesmentioning
confidence: 99%
“…The debate on total knee replacement (TKR) is therefore always more intense in order to perfect the technique. [2][3][4] The focus is on many variables that can affect the outcomes of TKA, including preoperative clinical plan, implantation technique, selection of implant materials and intra-and postoperative strategies. [5][6] In the following discussion, our review is located and focused on the application of postoperative intraarticular wound drainage in total knee prosthetics.…”
Section: Introductionmentioning
confidence: 99%